The Hubungan word of mouth, kualitas pelayanan, kepuasan dan loyalitas pelanggan klinik rawat jalan bedah onkologi di Rumah Sakit Khusus Bedah X - Thomas Darwin; Ratni Prima Lita; Rima Semiarty (MEDIA ILMU KESEHATAN, 2022)
Background: Customer loyalty is absolutely necessary because without customer loyalty the hospital cannot develop, it can even experience a decline in business that threatens the existence of the hospital. But to achieve customer loyalty many influencing factors such as service quality, word of mouth and customer satisfaction.Objective: Therefore it is necessary to know which factors significantly affect customer loyalty, so that the hospital can develop effective and efficient program and strategies.Methods: This study is an explanatory research by examining relationship of the variables. Respondents in this study were 195 people that were customer of the Surgical Oncology Outpatient Clinic of X Surgical Specialty Hospital. Data processing using the SEM PLS Method with Smart PLS application.Results: The results show that service quality have a positive and significant direct effect to customer satisfaction and loyalty. Word of mouth also shows positive and significant direct effect to customer satisfaction and loyalty. But this study failed to prove a significant direct effect of customer satisfaction to customer loyalty.Conclusion: We can significantly increase customer satisfaction and customer loyalty by increasing service quality and improve word of mouth activity. However customer satisfaction is not a significant factor for customer loyalty